Software developed for polynomial cams design and analysis (2010)
The numerical design of cams that lead to their final manufacture has always been associated with much tedium and time consuming mathematical and graphical procedures. This is due to the number of lengthy equations and many design options involved in such design processes. Therefore, in this work, a significant contribution has been made in cam system design and analysis, by developing a software package and applying it to the analysis of polynomial cams. Two critical parameters associated with the design and manufacturers of cam systems have been analyzed; the prime circle radius of the cam and face width of the follower. Precisely, the effect of using the 3-4-5 and 8th- order polynomial functions on the two parameters while designing plate cams with reciprocating flat face followers has been analyzed in this work. Results show that these two parameters are directly influenced by the type of cam angular segments in the optimum design and final manufacture of cam system. In this work reliable software capable of performing extensive optimum design analyses when properly utilized has been developed.